Pendampingan Sekolah Binaan Standar Penjaminan Mutu Internal LPMP Provinsi Kalimantan Timur - Soerjo Adi Poernomo; Syafrudin Januar (Literasi Nusantara Publisher, 2022)
The purpose of developing the Internal Quality Assurance Standard for the Targeted Schools and their impact is to improve the quality of education by national education standards and to create a culture of quality education in the education unit. This community service activity aims to assist the target schools in implementing internal quality assurance standards in their schools so that they become more qualified. This activity uses the In-On-In method which is carried out online and offline. The results of this activity indicate that the implementation of the internal quality assurance system in the target schools requires the cooperation of all parties. With the implementation of quality assurance standards, it is hoped that educational units can meet standards that are still weak or do not meet national education standards or even exceed them.